Peningkatan Kemampuan Desain Grafis untuk Meningkatkan Kreativitas Dakwah pada PC IPM Medan Area - Faizal Hamzah Lubis; Fadhil Pahlevi Hidayat; Sigit Hardiyanto (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Living in the digital age makes graphic design one of the skills that people, especially teenagers, must have. Graphic design can be a necessity in various fields, one of which is in the area of da'wah. Graphic design is an art form that has a goal as a form of a solution in solving communication problems by utilizing graphic elements, such as colors, lines, shapes, and others. As a designer, several things need to be prepared, such as insight, skills, sensitivity, and creativity. The areas of graphic design competence that must be mastered are attitudes, knowledge, skills, sensitivity, talent, and creativity to produce various exciting forms of work. Then, someone who has design skills must be strategic and tactical by; having the skills or abilities for graphic design not only can increase creativity or the artistic ability for someone but can also be a way to increase one's creativity in designing messages or content, which is used as da'wah which can broadcast Islamic teachings and Muhammadiyah values in today's digital era. Through this activity, PC IPM Medan Area will gain knowledge, understanding, and create graphic designs.